Hemolytic anemia repressed hepcidin level without hepatocyte iron overload: lesson from Günther disease model - Millot, Sarah (Haematologica, 2017)
Hemolysis occurring in hematologic diseases is often associated with an iron loading anemia. This iron overload is the result of a massive outflow of hemoglobin into the bloodstream, but the mechanism of hemoglobin handling has not been fully elucidated. Here, in a congenital erythropoietic porphyria mouse model, we evaluate the impact of hemolysis and regenerative anemia on hepcidin synthesis and iron metabolism. Hemolysis was confirmed by a complete drop in haptoglobin, hemopexin and increased plasma lactate dehydrogenase, an increased red blood cell distribution width and osmotic fragility, a reduced half-life of red blood cells, and increased expression of heme oxygenase 1. The erythropoiesis-induced Fam132b was increased, hepcidin mRNA repressed, and transepithelial iron transport in isolated duodenal loops increased. Iron was mostly accumulated in liver and spleen macrophages but transferrin saturation remained within the normal range. The expression levels of hemoglobin-haptoglobin receptor CD163 and hemopexin receptor CD91 were drastically reduced in both liver and spleen, resulting in heme- and hemoglobin-derived iron elimination in urine. In the kidney, the megalin/cubilin endocytic complex, heme oxygenase 1 and the iron exporter ferroportin were induced, which is reminiscent of significant renal handling of hemoglobin-derived iron. Our results highlight ironbound hemoglobin urinary clearance mechanism and strongly suggest that, in addition to the sequestration of iron in macrophages, kidney may play a major role in protecting hepatocytes from iron overload in chronic hemolysis.